KONTRIBUSI PT MRT (MASS RAPID TRANSIT) JAKARTA DALAM PELAKSANAAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) TUJUAN KE-13 - Fitriani, Tessha; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
SDGs is an international environmental regime which serves as a guideline for international actors to carry out sustainable development in 2015-2030 by balancing economic aspects, social aspects and environmental aspects with the establishment of 17 goals and 169 targets which are measured through 241 indicators. To realize all SDGs goals, contributions from all stakeholders including the business world are needed, as is done by PT. MRT Jakarta. As a provider of public transportation facilities, PT. MRT Jakarta is aware that pollution resulting from burning motorized vehicles is the biggest contributing factor to climate change, which is the 13th goal of the SDGs. This research will look at how PT. MRT Jakarta's efforts to implement SDGs goal 13. This research uses CSR theory and group level analysis. This theory explains that CSR is a company's step in achieving balance in company goals. There are 3Ps that are the focus in implementing CRS, namely profit, people and planet. The research method used is a qualitative method with data collection techniques obtained from literature studies, namely through annual reports, research reports and data from official websites, journals and books. The results of this research show that as a corporation in the field of public transportation services, you not only expect profits, but also participate in community welfare and care for the environment and social issues. Therefore, as a company PT MRT Jakarta implements SDGs which are in line with the company's steps to achieve balance and sustainability of company goals which focus on 3P, namely Profit, People, Planet. Keywords: PT MRT Jakarta, SDGs, CSR, Climate Change